PENGARUH PENERAPAN SISTEM INFORMASI AKUNTANSI MANAJEMEN DAN PENGENDALIAN KUALITAS PRODUK TERHADAP KINERJA PERUSAHAAN PADA PT MITSUBA PLAN 2 CIKANDE – SERANG - Navita Yuliana; Nugrahini Kusumawati; Efi Tajuroh Afiah (Nindikayla Institute, 2023)
In a company, company performance is one of the most important things that must be achieved, the application of management accounting information systems and product quality control is one of the supports for company performance. This study aims to determine the effect of the application of management accounting information systems and product quality control on company performance at PT Mitsuba Plan 2 Cikande – Serang either partially or simultaneously. The research method used is quantitative, using non-probability sampling technique with a population of 150 employees with the sample used is 60 employees and processed with SPSS Version 2.4. The results of testing the first hypothesis (H1) tcount > t table or 7,267 > 2,001 with a significance level of 0.000 < 0.05 then Ha is accepted and Ho is rejected (H2) tcount > t table or 5.430 > 2.001 with a significance level of 0.000 < 0.05 then Ha accepted and Ho is rejected (H3) the value of Fcount > Ftable, (27.042 > 3.16) with a significance level of 0.000 <0.05, it can be concluded that Ha is accepted and Ho is rejected Based on the test, it is concluded that the application of accounting information systems affects the company's performance and product quality control affects the company's performance and simultaneously affects the company's performance